Is the scientific method a myth? Perspectives from the history and philosophy of science - Elliott Sober (Mètode Science Studies Journal: Annual Review)
Many philosophers and historians of science deny that there is a single scientific method that applies across all scientific disciplines. Here I distinguish normative from descriptive versions of this thesis. I defend the thesis that there are general normative principles that govern every science.